Histology for the visually impaired: A study applying models at Universities in Spain and Brazil - Comarú, Michele Waltz (2021)
This study aimed to develop models that reproduce histological slide images and evaluate them with blind and sighted students from an inclusion perspective. A questionnaire with questions about the ideal characteristics of a model was answered by visually impaired (VI) students. Based on the responses and optical microscopy images from histological atlases, nine models were constructed with standardized materials. The models were tested at different times with VI students and with students who see. Our results indicate that morphology teaching, according to the students themselves, should make use of extra resources, such as models. The ideal characteristics for model efficiency as a teaching tool were representative textures and reliefs. The models built were evaluated by blind students in Spain and sighted students in Brazil because, from an inclusive perspective, it is ideal that the same material can meet the demands of all types of students. The use of the developed models enhanced learning in both groups, even when combined with microscopes for sighted students. According to student opinions, the use of relief models can represent an important pedagogical strategy used to teach morphological. The importance of developing that materials was also highlighted from an inclusion perspective, as these materials can be used in mixed classes, all students together, in cooperative learning. This study aids morphological subject teachers who teach visually impaired students to know where to start on the path to an inclusive and pedagogically coherent learning process.